Ultrathin sheets of metal or metal sulfide from molecularly thin sheets of metal thiolates in solution - Busupalli, Balanagulu; Kummara, Sreenivas; Kumaraswamy, Guruswamy; Bhagavatula L. V. Prasad (Chemistry of Materials, 2014)
Materials that exist as single molecule thick twodimensional sheets are in great demand because they hold promise as precursors for synthesis of layered functional materials. We demonstrate that metal thiolates, that exist as lamellar assemblies in the neat state, can be disassembled into individual molecular sheets simply by dilution in apolar organic solvents and that these can form ultrathin metallic layers on substrates upon heat treatment. We establish the pathway to the disassembly of metal thiolates in solution using a combination of techniques, including X-ray diffraction, light scattering, FTIR, and TEM. Our results indicate that the lamellar structure of Pd-thiolates is preserved in toluene up to a concentration of 300% w/v and the average intersheet distance is unchanged. Interestingly, the dynamics of the Pd-thiolate sheets remain correlated even on diluting them up to 30% w/v, though the disorder within the lamellar stacks increases with a decrease in their coherence length. Finally, at dilutions less than about 5% w/v, individual sheets of these structures can be accessed that are isolated and directly observed using TEM. Heat treatment of the ultrathin films of metal thiolates deposited on appropriate substrates resulted in the formation of metal or metal sulfides with retention of sheetlike morphologies.

Preparation of Ni3S2 and Ni3S2-Ni nanosheets via solution based processes - Busupalli, Balanagulu; Date, Kalyani S.; Datar, Suwarna; Bhagavatula L. V. Prasad (Crystal Growth & Design, 2015)
An easy and convenient preparation of nanometer-thick sheets of Ni3S2 and Ni3S2–Ni from solution processed molecularly thin sheets of Ni-thiolates is described. Both the Ni3S2 and Ni3S2–Ni possessed sheet-like morphologies and displayed room temperature ferromagnetic characteristics. The ferromagnetic nature of these samples was also confirmed by MFM studies, and AFM/TEM investigations substantiated the sheet-like morphology of the samples.

Synthetic biological circuits: digital or analog? - Busupalli, Balanagulu (Current Science, 2015)

In situ electrochemical transformation of Ni3S2 and Ni3S2-Ni from sheets to nanodisks: towards efficient electrocatalysis for hydrogen evolution reaction (HER) - Busupalli, Balanagulu; Battu, Shateesh; Haram, Santosh K.; Bhagavatula L. V. Prasad (Chemistryselect, 2016)
Transition metal sulphides have been viewed as alternatives to platinum based electrocatalysts for HER. Herein, we report the preparation of Ni3S2 in conjunction with Ni in a novel nanosheet morphology and verified its performance for HER. During cyclic polarization, exotic morphological transformation of Ni-3 S-2-Ni from nanosheets to nanodisks has been noted. This change is accompanied with initial increase in over-potential that passed through maxima (similar to 100mV above the starting potential) and decreased to similar to 50mV below the starting value. Enhanced electrocatalytic activity due to the morphological changes from sheets to nanodisks has been attributed to the formation of more number of exposed edge-planes known to promote HER. Kinetic analysis based on Tafel slope displayed by this composite is comparable to that of Pt based catalysts.

Solvent-less solid state synthesis of dispersible metal and semiconducting metal sulfide nanocrystals (vol 6, pg 12006, 2018) - Bera, Abhijit; Busupalli, Balanagulu; Prasad, Bhagavatula L. V. (ACS Sustainable Chemistry & Engineering, 2020)